The Diversity of Tourism in Iraq and its Impact on Achieving Sustainable Tourism Development: An Analytical Study of Opinions from a Sample of Tourist Hotels in Baghdad Governorate: Keragaman Pariwisata di Irak dan Dampaknya terhadap Pencapaian Pembangunan Pariwisata Berkelanjutan: Studi Analitis terhadap Pendapat dari Sampel Hotel-Hotel Wisata di Provinsi Baghdad - Maseer, Dr. Rasool Salim (Indonesian Journal of Public Policy Review, 2026)
Background: In many destinations, reliance on limited tourism products creates challenges for sustainability and competitiveness. Knowledge Gap: There is limited integrated analysis of how tourism product diversification aligns with sustainable planning frameworks and destination management strategies. Aims: This study aims to examine the role of tourism diversification in supporting sustainable destination development through planning and management approaches. Results: The findings indicate that diversified tourism products contribute to broader economic opportunities, improved resource utilization, and increased resilience of destinations. Strategic planning and stakeholder involvement are identified as key elements in achieving balanced development. Novelty: This study provides a conceptual integration of tourism diversification and sustainable planning, emphasizing their interconnected roles in destination management. Implications: The results suggest that policymakers and planners should adopt comprehensive diversification strategies supported by sustainable frameworks to ensure long-term destination viability and competitiveness. Keywords: Tourism Diversification, Sustainable Tourism, Destination Development, Tourism Planning, Economic Growth Key Findings Highlights Broader product offerings support economic stability Planning frameworks guide balanced resource allocation Stakeholder roles shape long term destination outcomes